Proposed scenario for post-suicide attempt care for individuals undergoing gender transition - Vitória Alexandrina Volpe; Aline Conceição Silva; Laysa Fernanda Silva Pedrollo; Lucca de Oliveira Rosa; Manoel Antônio dos Santos; Elton Carlos Almeida; Kelly Graziani Giacchero Vedana (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To develop and validate a simulated scenario for post-suicide attempt care for a person undergoing gender transition. Method This was a methodological study conducted in two stages: (i) development of the scenario based on the literature and clinical simulation recommendations; (ii) validation by ten experts, through an online assessment using a Likert scale and suggestions. Descriptive analyses and content validity index were applied. Results : All items met the minimum acceptance criterion (≥0.70), and adjustments were made to incorporate a more inclusive approach and reflect the diversity of gender identities. Conclusion The study developed and validated a clinical simulation scenario for post-suicide attempt care for a person undergoing gender transition. The expert validation indicated agreement on the scenario’s items, which can be applied in accessible training and qualification for healthcare professionals across different categories and contexts.